Regional identity and its protection on the example of the Valencian Autonomous Community - Głuszek-Szafraniec, Dagmara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article systematizes the knowledge about the Valencian Autonomous Community and the activities of its authorities in the field of language policy. The author has reviewed the legal solutions strengthening the status of a regional language in public space and discussed the main laws that emphasize the importance of the language as a cultural heritage of Valencia.
Keywords: regional identity; autonomous community; language policy; Spain; media system